Gerakan Perempuan Subaltern Ekofeminisme dalam Melawan Pembangunan PLTU 2 Indramayu - Cusdiawan Cusdiawan; Oekan S. Abdoellah; Firman Manan (Mahesa Research Center, 2022)
This research examines the struggle of women in rejecting development that is considered damaging to the environment. The problem asked in this study, namely